Capital flows-at-risk - Eguren-Martin, Fernando,O'Neill, Cian,Sokol, Andrej,Berge, Lukas von dem (European Central Bank, 2021)
We characterise the probability distributions of various categories of gross capital flows conditional on information contained in financial asset prices in a panel of emerging market economies, with a focus on
10.2866/897820
Keywords: Graue Literatur; capital flows; sudden stops; capital flight; retrenchment; capital flow surges; push versus pull; capital controls; macroprudential policy; nancial conditions indices; quantile regression